Proceso del programa de fitomejoramiento de frijol, Phaseolus vulgaris, en CIAT - Robledo, A; Hernández Bravo, Guillermo (International Center for Tropical Agriculture, 1974)
The work done by CIAT`s bean breeding program has as its basic objective the production of bean populations and lines with high yielding potential. With a germplasm bank consisting of 9,413 introductions of P. vulgaris at present, it has been possible to conduct adaptation studies under 4 different environments with different ecological conditions. The genotypes, selected for their wide range of adaptation and their yield potential, will be included in the formation of the 1st genetic populations or composites in beans. (AS-CIAT)